The Relationship between the Smart Indonesia Card (KIP), Social and Demographic Characteristics, Mean Years of Schooling (MYS), and GRDP per Capita in Indonesia - Taufik Hidayat; Triaswati, Ninasapti (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the impact of the Smart Indonesia Card (KIP) on Mean Years of Schooling (MYS) and economic welfare, using panel data from 511 Indonesian regions (2020–2023) and a fixed effects model. Results show KIP significantly increases MYS after two years and indirectly boosts GRDP per capita via education. Spatial analysis reveals stronger impacts in Western Indonesia and in developed or lagging regions. Sociodemographic factors and complementary programs like BOS and DAK strengthen outcomes. Findings underscore the need for place-based policy refinements to enhance KIP’s effectiveness in promoting equitable educational and economic progress.